Microscopic Observation of Solid-Liquid Reaction: A Novel Laboratory Approach to Teaching Rate of Reaction - Agus Setiabudi; Asep Wahyudin; Galuh Yuliani; Mauro Mocerino (Universitas Gadjah Mada, 2017)
The importance of observation in science and science education has triggered this laboratory development study that investigated the value of an observation kit as a new approach to teaching rate of reaction in general chemistry class. The kit consists of a digital microscope, a “chemical reactor”, and a tailor-made computer application and was used to video-record a solid-liquid reaction and to produce a series of two dimensional solid images that indicate the extent of reaction. The two dimensional image areas were calculated by the computer application and using the assumption that the image area was directly proportional to the mass of the solid, a plot of solid mass versus time could be obtained. These steps have been tested in several solid-liquid reaction systems, with the reaction of solid magnesium oxide with nitric acid solution resulting in the best images which were transferable to rate of reaction data, i.e. a plot of solid MgO mass as a function of time. The plot can be used to explain rate of reaction concepts including average, instantaneous, and initial rate. Furthermore, the effect of concentration on reaction rate could also be explained. This study showed that the observation kit and the generated data set have the advantage of allowing students to clearly and repeatedly visualise a solid-liquid reaction and relate this with the concept of rates of reactions. The observation kit also allows teachers and students to extend its application into inquiry based experiments.